Faunal Composition of Soil Cryptostigmata (Acari: Arthropoda) in Different Ecosystems of Cachar District, North Eastern India - Ray, D. C.; Manoranjan Singh, S.; Amarjit Singh, L. (Indian Forester, 2013)
Present study explored the diversity of soil oribatid in four different ecosystems Cachar district of Assam, during July, 2009. Oribatid microarthropod were dominant in homegarden (35.45%), whereas members of Trhypochthoniidae were found to be higher in teak plantation (24.03%). Findings suggest that the members of oribatulidae family are most resistant survivor under different land used practices. Density of total cryptostigmatid mites showed decreased order from the undisturbed site to disturbed sites (forest>secondary succession>homegarden>teak plantation). Species similarity of oribatid mite associations in 4 study habitats found that maximum was (45.00%) between secondary succession and forest site and minimum between the teak plantation and homegarden (7.14%). Study concludes that oribatid mites could not be used as an absolute bioindicator of land use types.